Home-Based Management of Acute Upper Respiratory Tract Infections in Preschoolers of Virac, Catanduanes: Analysis of Caregivers' Knowledge - Tabuzo, Aeshel; LAREZA, MA. FRANCIA; RAZAL, CHRISTINE; MENDOZA-BAYOS, PAMELA; VERA , ZACARIAS III (Alta Dharma Publisher, 2024)
Background: Health extends beyond the mere absence of illness; it encompasses holistic well-being, including physical, mental, and social dimensions [1]. Objective: This study investigates the knowledge of caregivers regarding the home-based management of Acute Upper Respiratory Tract Infections (AURTIs) in preschoolers in Virac, Catanduanes. Methods: Using a descriptive correlational design, the study surveyed 319 caregivers of children aged 3 to 5 years enrolled in Day Care Centers from 52 barangays out of 63 of Virac, Catanduanes. The research aimed to profile the respondents, assess their knowledge and determine barriers faced in managing AURTIs at home, and examine correlations between these factors. Data were collected using a questionnaire and analyzed using percentage techniques, weighted means, and Pearson correlation coefficients. Results: Key findings include a predominance of female caregivers, significant diversity in marital status, and varying levels of education and household income among respondents. Conclusion: The study highlights the crucial role of caregivers in child health management and proposes strategies to improve their knowledge. The insights gained aim to guide future interventions to enhance caregiver education, ultimately improving child health outcomes and reducing the burden of AURTIs on families and healthcare systems.